Diterpenos y otros constituyentes de Croton hirtus (Euphorbiaceae) - Fuentes, J C (Universidad de Costa Rica, 2004)
The roots of Croton hirtus (Euphorbiaceae) collected in Paraiso, Cartago (Costa Rica) afforded, in addition to the few known metabolites, 20 new compounds: the bis-nor dolabradane 1, the dolabradanes 2 and 3, the kauranes 4-7, the cyclopropakauranes 8 and 9, the hirtusanes 10-15, the germacradiene esters 16-18 and the C-25 compound 21, presumably formed by a Diels-Alder reaction between compound 18 and a monoterpene. All structures were elucidated using high field 1D and 2D NMR techniques. MS fragmentation patterns are here reported. The absolute configurations of 4 and 9 were elucidated by using circular dichroism. The separation was performed with modern chromatographic technics.